Investigation of the performance of cement mortar incorporating lithium slag as a super-fine aggregate - Dong, Shuangkuai; Tu, Shengwen; Chen, Liangliang; Wu, Fufei; Xie, Lilan; Zhuo, Qi; Yu, Songhan (Frontiers in Materials, 2023)
As a by-product of lithium salt mining, the emission of lithium slag increases yearly due to increased demand. Therefore, the utilization of lithium slag faces a huge challenge. In this study, a new approach to using lithium slag as a super-fine aggregate in cement systems was proposed. The use of lithium slag as a super-fine aggregate replacing 0%, 30%, 50%, 70%, and 100% of the standard sand was tested. The main hydration products of cement–lithium slag paste were calcium silicate hydrate gel, calcium hydroxide, unhydrated particles, and a small amount of ettringite. Lithium slag as a super-fine aggregate could significantly reduce the dead load of structures, enhance flexural and compressive strength and the peak stress of mortar, and no more than 50% lithium slag could significantly enhance the permeability of mortar. The study revealed that the replacement rate of lithium slag as a super-fine aggregate could reach 50%, which is five times more than the amount used as supplementary cementitious material. Therefore, the study brings an innovation in the use of lithium slag in cement systems and improves the performance of cement mortar.